The Fright of the Phonos: the Voice in 'The Battle of Algiers' - Laurent Shervington (Limina: A Journal of Historical and Cultural Studies, 2020)
'The Battle of Algiers' is a film that chronicles the conflict between the French colonial military and the Algerian revolutionaries during the Algerian war (1954–1962). A post-independence work, Pontecorvo’s film is dedicated to the events of 1957, with flashbacks, amateur actors, and grainy neo-realist footage underpinning the director’s approach. The film is also renowned for its sonic elements, with sounds of armed conflict, explosions, and engines adding to the realist parameters of the film. In terms of soundtrack, muted guitars and rhythmic drumming are central to significant scenes. While these elements are certainly crucial to the construction of the narrative, this article focuses on the sonic element of the voice, which I claim marks a site of rupture within the film. Following the Lacanian understanding of the voice, I maintain in this article that it is the omission of an adequate analysis of the voice in 'The Battle of Algiers' that leads theorists to overlook the genuine emergence of rupture within the film.